Freedom and responsibility levels: systems analysis - V. N. Sagatovsky (Бюллетень сибирской медицины, 2006)
There are three essential freedom interpretations. They are represented as complementary levels of integral freedom compre- hension. The first level is represented with the outer trends of existence and civil responsibility perception. This level objectifies the art implementation of the free choice. Human freedom as the choice and responsibility for it is carried out at the second backbone level — the level of freedom and responsibility as an entire phenomenon. The third top level is forming with a presence of the Spirit in human choice tendency and creativity, who accepts the responsibility before the entity spiritual reasons. Human soul mission, sacring by the Spirit presence, is free and liable the man, the word, the objective and subjective actuality advancing. Though this fundamental choice between Good and evil only by man himself could be made.